A Critical Review Of The Effectiveness Of Economic Policies During The Pandemic In Developing Countries - Apriyasni Melati; Sri Umiatun Andayani; Adisti Maharani Krisna; Ni Wayan Septia Wini; Faty Rahmarisa (Rey Media Grafika, 2025)
This study examines the effectiveness of economic policies in addressing global economic challenges and their impact on various sectors, including SMEs and the informal sector. The primary focus is on analyzing how fiscal and monetary policies can mitigate economic instability and enhance public welfare. The study also explores the role of digital technology in supporting transparency and efficiency in economic policymaking. The research employs both qualitative and quantitative approaches, utilizing secondary data analysis from reliable sources. The findings indicate that strong coordination between central and local governments, along with responsive and inclusive economic policies, can enhance the effectiveness of economic strategies. This research is expected to serve as a foundation for more adaptive economic policies in the future.